Digital Bookkeeping for MSMEs: A Review and SWOT Analysis - Hidayati, Irma (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This research explores the critical integration of digital accounting tools in the operations of Indonesian MSMEs. This research explores existing research through a systematic literature review and conducts a SWOT analysis on SIAPIK and LAMIKRO applications. There are 19 research articles analyzed related to digital bookkeeping applications, divided into two discussions: empirical findings and research gaps. SWOT analysis is presented to understand digital bookkeeping applications' strengths, weaknesses, advantages, and threats. Finally, recommendations for future research are presented.